PENERAPAN KONSEP HUKUM BERNOULLI UNTUK MENGATASI KRISIS AIR PADA KELOMPOK TANI PADI JORONG BATU GADANG DI KENAGARIAN KATIALO KABUPATEN SOLOK, SUMATERA BARAT - Marzuki Marzuki; Ahmad Fauzi Pohan; Afdal Afdal; Trengginas Eka Putra Sutantyo (Jurnal Hilirisasi IPTEKS, 2021)
This activity aims to apply Bernoulli's law to the piping system in the hydrant pump to meet the needs of residents in bathing, washing, and irrigating the fields. The activity begins with conducting a site review survey, counseling and determining the location of pump placement, making pumps and towers, and lifting pumps and towers to the location. Then the activities at the location are divided into several parts, including the manufacture of civil and mechanical pump systems and testing the success of the pump system. This activity carried out the manufacture of hydrant pumps by installing pipes using Bernoulli's law to meet the needs of the residents of Jorong Batu Gadang, totaling 30 families and irrigating rice fields covering an area of 78 ha, which are rainfed rice fields. The results of the activities carried out at Nagari Katialo, Jorong Batu Gadang in applying the concept of Bernoulli's Law to the piping system at the hydrant pump made water faster to reach the highest point of the piping system that had been made. As for the difference in height between the position of the pump and the water level in the reservoir (tank) of 30 meters, the flow of water rising to the tank is 2 liters/second. The people of Jorong Katialo can already enjoy the water stored in the reservoir. The success of this pump system is shown from less than 10 minutes of testing the water successfully to the water reservoir above the tower with a height difference of 30 meters from the placement of the hydrant pump.